HUBUNGAN ANTARA KARAKTERISTIK WANITA DENGAN KELUHAN PADA MASA MENOPAUSE DI WILAYAH KERJA UPK PUSKESMAS PERUMNAS II PONTIANAK - Diena Juliana; Dwi Anggraini; Nurul Amalia (Borneo Nursing Journal (BNJ), 2021)
Menopause is a phenomenon in the life of women characterized by the menstrual cycle where the ovary cessation or ovaries have impairment in the functions of esterogen so hormone levels in women being inferior.This means menopause women to physical and psychological keluhan-keluhan.Complaints from at menopause varied individual and was in nature, because some of are affected are the education level, economic social levels, lifestyle, for example smoking or drink alcohol, the local culture, and the use of contraceptive you. Know the relation between characteristic of a woman with complaints at menopause in the work area for Puskesmas UPK II Kota Pontianak. The kind of research this is quantitative , use the analytic method with the approach cross sectional .96 research sample areas respondents and using a technique the sample collection which is purposive the sampling method of .Use logistic regression test data available for analysis. The results of this study indicate that there is a relationship between age at menopause (p = 0.031, OR = 5,527), level of knowledge (p = 0.009, OR = 4, 575), history of use of hormonal contraceptives (p = 0.004, OR = 7.730) and complaints. at menopause. There is no relationship between education level (p = 0.107, OR = 2.510), occupation (p = 0.345, OR = 1.796). Complaints of menopause are not the same for every woman, depending on her readiness and how she reacts to it. It is recommended that health workers be able to provide counseling about menopause to women who have not menopause and who have already menopause so that all of them can accept the arrival of menopause and not feel worried about what they are experiencing.